6x-71=x+4

Simple and best practice solution for 6x-71=x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-71=x+4 equation:



6x-71=x+4
We move all terms to the left:
6x-71-(x+4)=0
We get rid of parentheses
6x-x-4-71=0
We add all the numbers together, and all the variables
5x-75=0
We move all terms containing x to the left, all other terms to the right
5x=75
x=75/5
x=15

See similar equations:

| F(x)=8(3)^x | | v-22=2v-96 | | 5x-40=2x-13 | | 3x+2x+25=90 | | |x-2|+|x+2|=0 | | 4/5x=61/3 | | 11x-63=2x | | 9^(m-6)=78 | | 18m+50=1,940 | | 7.5=-2.5-(1+2n) | | 5r-13=12 | | V=0.3×0.5×0.02=x | | 12m+100=1,229 | | 14=11+w8.6 | | 1x(-4)=10 | | 0.5×0.3×0.02=0.003=v | | 2-0.75m=5 | | 2=6(x−3)+4−5x | | -2x-14=6(x+7) | | 1.47=x^2 | | 36m+200=9,500 | | 2=4r-14.2 | | -38=-8+6y-12 | | c-20=12 | | 7p-8=3(3p-5) | | 4^x/2=8 | | 0.02+0.5a=-0.3 | | 12p=3=11 | | -2(z+4)-(3z-2)=-2-(6z-2) | | -7x—5=9 | | t-23+6t=3(3t-9) | | 6(3x–9)=–18 |

Equations solver categories